Diversity of Bivalve and Gastropod, Molluscs of some localities from Raigad district, Maharashtra, west coast of India. - N, Khade S; Mane, U H (Recent Research in Science and Technology, 2012)
Diversity of bivalve and gastropod molluscs from mangrove habitat, rocky substrata, sandy beach, and muddy habitat was studied. 22% bivalves while 78% gastropods were recorded during October 2010 to September 2011. The numbers of molluscs was comprised of bivalve species namely Crassostrea cattuckensis, Saccostrea cucullata, Anadara granosa, Meretrix meretrix, and gastropods Planaxis sulcatus, Littorina scabra, Dostia violacea, Cerithium cingulata,Telescopium telescopium, Nodilittorina melanostoma and Casidula nucleus were dominant, The productive molluscan fauna in prevalence of different habitats so a wide chance of research to further explore on the possibility of ecological value and there conservation.